Efecto de luz azul en sanidad de zanahoria mínimamente procesada - Diaz, Mariano Emanuel; Rodriguez Romera, Mariela Carmen; Gonzalez Erbin, Omar Adrian; Bazterra, Delfina; Rodoni, Luis Maria (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster